Caspase-3-mediated Cleavage of Cdc6 Induces Nuclear Localization of p49-truncated Cdc6 and Apoptosis - Yim, Hyungshin (The American Society for Cell Biology, 2003)
We show that Cdc6, an essential initiation factor for DNA replication, undergoes caspase-3–mediated cleavage in the early stages of apoptosis in HeLa cells and SK-HEP-1 cells induced by etoposide, paclitaxel, ginsenoside Rh2, or tumor necrosis factor-related apoptosis-inducing ligand. The cleavage occurs at the SEVD(442)/G motif and generates an N-terminal truncated Cdc6 fragment (p49-tCdc6) that lacks the carboxy-terminal nuclear export sequence. Cdc6 is known to be phosphorylated by cyclin A-cyclin dependent kinase 2 (Cdk2), an event that promotes its exit from the nucleus and probably blocks it from initiating inappropriate DNA replication. In contrast, p49-tCdc6 translocation to the cytoplasm is markedly reduced under the up-regulated conditions of Cdk2 activity, which is possibly due to the loss of nuclear export sequence. Thus, truncation of Cdc6 results in an increased nuclear retention of p49-tCdc6 that could act as a dominant negative inhibitor of DNA replication and its accumulation in the nucleus could promote apoptosis. Supporting this is that the ectopic expression of p49-tCdc6 not only promotes apoptosis of etoposide-induced HeLa cells but also induces apoptosis in untreated cells. Thus, the caspase-mediated cleavage of Cdc6 creates a truncated Cdc6 fragment that is retained in the nucleus and induces apoptosis.